Reducing Effect of Saikosaponin A, an Active Ingredient of Bupleurum falcatum, on Intake of Highly Palatable Food in a Rat Model of Overeating - Maccioni, Paola; Fara, Federica; Gessa, Gian Luigi; Carai, Mauro A. M.; Chin, Young-Won; Lee, Jung Hwan; Kwon, Hak Cheol; Colombo, Giancarlo (Frontiers in Psychiatry, 2018)
Recent lines of experimental evidence have indicated that saikosaponin A (SSA) – a bioactive ingredient of the medicinal plant, Bupleurum falcatum L. – potently and effectively reduced operant self-administration of chocolate and reinstatement of chocolate-seeking behavior in rats. The present study was designed to assess whether the protective properties of SSA on addictive-like, food-related behaviors generalize to a rat model of overeating of palatable food. To this end, rats were habituated to feed on a standard rat chow for 3 hours/day; every 4 days, the 3-hour chow-feeding session was followed by a 1-hour availability of highly palatable, calorie-rich Danish butter cookies or Oreo chocolate cookies. Even though fed, rats consumed large amounts of cookies; intake of calories from cookies (consumed in one hour) was even larger than that of calories from chow (consumed in 3 hours). SSA (0, 0.25, 0.5, and 1 mg/kg, i.p.) was administered 10 min before cookie presentation. Treatment with SSA resulted in a dose-related decrease in intake of both butter and chocolate cookies. Administration of the cannabinoid CB1 receptor antagonist/inverse agonist, rimonabant (0, 0.3, 1, and 3 mg/kg, i.p.; tested as reference compound), produced a similar reduction in intake of butter cookies. These results (a) contribute to the set-up and validation of a rat model of overeating, characterized by the intake of large amounts of unnecessary calories and (b) provide an additional piece of evidence to the anorectic profile of SSA in rats.